How to Apply Android Applications (Edmodo) and Google Forms as Learning Media in Historical Learning in High School - Usman Usman; Tengku Muhammad; Bagus Endri Yanto (STAI Hubbulwathan Duri, 2022)
The learning that has been carried out so far, both conventionally and those who have implemented e-learning using computer devices, then slowly changes to mobile-based learning by utilizing smartphones and tablets. The use of ICT in history learning is expected to further increase students' understanding of the material being studied. The purpose of this study is to analyze how teachers apply edmodo and google forms as learning media in historical learning. The method used is descriptive analysis with a qualitative approach. The researchers collected the data throught literature review and analyzed them using content analysis technique. The data analysis stages comprised data reduction techniques, data presentation, and conclusion drawing. In addition, the development of this media can be done by the teacher independently. The use of edmodo and Google forms can be used as evaluation tools for history learning in high school. Learning by utilizing edmodo and google forms and sent to students via social media is expected to be able to overcome the limitations of teachers in distance learning